REVITALISASI TULISAN ARAB-JAWI DALAM PEMBELAJARAN BAHASA DAN SASTRA INDONESIA DI SEKOLAH DASAR PROVINSI ACEH - Wardani, Vera (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
This study aims to revitalise the use of the Arab-Jawi script in the teaching of Indonesian Language and Literature at the primary school level, as part of efforts to preserve cultural heritage and strengthen literacy grounded in local wisdom. Arab-Jawi, an adaptation of the Arabic script to the phonological system of the Malay language, once served as a cornerstone of literacy among Malay-Muslim communities, including in Aceh. However, its role has been marginalized due to the dominance of the Latin alphabet. Employing a qualitative approach with an educational case study method, this research was conducted in three primary schools in Pidie Regency. Data were gathered through classroom observations, interviews, document analysis, and focus group discussions, and analysed thematically. Findings indicate that although Arab-Jawi is not yet formally included in the national curriculum, several teachers have taken the initiative to teach it using classical manuscripts, writing exercises, and cultural value discussions. Key challenges include limited learning resources and insufficient teacher training. Policy support, the development of instructional modules, teacher training programmer, and the digitisation of classical texts are essential to ensure the sustainability of this initiative.